2016
DOI: 10.21475/ajcs.2016.10.05.p7167
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic characteristics associated with the normalized difference vegetation index (NDVI) in the peanut crop

Abstract: Advances in agricultural technology have led to the development of active remote sensing equipment that can potentially estimate components of crop production; however, this assessment is still in its early stages for the peanut crop. The objective of this study was to evaluate the normalized difference vegetation index (NDVI) generated by a terrestrial sensor and its relationship with agronomic variables of peanut crops grown at different densities. The parameters evaluated were the NDVI, pod yield, mass of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(19 reference statements)
1
9
0
4
Order By: Relevance
“…The biomass estimate was not as accurate as the grain yield estimate. In peanut, Zerbato et al (2016) reported an R 2 of 0.27 in the estimation of crop biomass, whereas, in rice and barley, the highest R 2 Figure 5. Performance of the models using the IRVI in the estimation of white oat grain yield at the stages 4 (a), 8 (b), 10 (c) and 10.5.4 (d), according to the phenological scale of Feeks and Large (Large 1954).…”
Section: Resultsmentioning
confidence: 94%
“…The biomass estimate was not as accurate as the grain yield estimate. In peanut, Zerbato et al (2016) reported an R 2 of 0.27 in the estimation of crop biomass, whereas, in rice and barley, the highest R 2 Figure 5. Performance of the models using the IRVI in the estimation of white oat grain yield at the stages 4 (a), 8 (b), 10 (c) and 10.5.4 (d), according to the phenological scale of Feeks and Large (Large 1954).…”
Section: Resultsmentioning
confidence: 94%
“…According to Amaral et al (2015a), many active optical sensors can be found, but there is little research comparing the efficiency of these devices for the determination of the parameters of cultures. Using terrestrial remote-sensing with the Normalized Difference Vegetation Engenharia Agrícola, Jaboticabal, v.39, special issue, p.33-40, sep. 2019 Index (NDVI) associated with agronomic characteristics of the peanut crop, it was previously verified that results obtained with the GreenSeeker sensor can be used to determine the population characteristics of plant cover and yield estimates, and as an additional tool for farmers to detect crop potential (Zerbato et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Zerbato et al (2016), evaluating the linear correlation between NDVI and peanut yield in the production of green and dry peanut mass, obtained positive linear regression and determination coefficients of 0.3161 and 0.2761, respectively. The low NDVI values were attributed to naked soil exposure between rows of plants.…”
Section: Treatmentsmentioning
confidence: 99%
“…One of the applications of the geotechnologies use is the estimation of agricultural productivity and the nutritional status of the crops in a fast and precise way, due to the close relation between these variables and vegetation indices (Zerbato et al, 2016). The high correlation between biomass accumulation and vegetation indices occurs due to the high levels of chlorophyll in the plant, which varies according to the environmental conditions and crop management, such as nitrogen application, resulting in increments of leaf area and photosynthetic activity (Grohs et al, 2011).…”
Section: Introductionmentioning
confidence: 99%